Health Related-Quality of Life in CKD and Dialysis Patients in Asian Countries : A Systematic Review - Aan Anjarwati (ARKESMAS [Arsip Kesehatan Masyarakat], 2018)
ABSTRACT Introduction: Chronic Kidney Disease (CKD) and Chronic dialysis has a great impact on patients health-related quality of life (HRQOL). The impacts are about the morbidity, mortality, and the survival rate of the dialysis therapy. We focused this systematic review in Asian countries. Methods: Systematic Review with PRISMA method retrieved from online database such as PubMed, Wiley and ProQuest using a keyword “Health Related-Quality Life (HRQOL)”, “Chronic Kidney Disease (CKD) patient OR ESRD (End Stage Renal Disease), CKD with Hemodialysis OR CKD dialysis at Asian Country”. The end of this search we got 10 journals. Results: The measurement HRQOL in CKD or dyalisis patients such EQ-5D and Kidney Disease Quality of Life (KDQOL). There are 4 country used KDQL (Korea, China, India, Singapore and Indonesia). The result show HRQOL in CKD patients has declined when the level of CKD increased especially when the amount of albumin high and the level of hemoglobin decline. HRQOL in dialysis patient has lower depressive mood in planned dialysis group than unplanned dialysis. There are no difference in KDCS, PCS, or MCS scores between patients treated by hemodialysis and CAPD. They also got 5 more years when choose dialysis (Hemodialysis). Conclusion: Health related quality of life (HRQOL) related with progressive of CKD level. The level that should pay attention is CKD level 3 where HRQOL can decreased. When the patients routine dialysis (CAPD or hemodialysis) used concern about the medicine (such erythropoietin, routine medicine) and the laboratory (albumin and hemoglobin). The more progressive level of CKD the lower of HRQOL. Keywords: Health Related Quality of Life (HQOL), CKD (Chronic Kidney Disease), Dialysis, Hemodialysis, Continuous Ambulatory Peritoneal Dialysis (CAPD).